Synchronization of Optomechanical Nanobeams by Mechanical Interaction - Colombano, M. F.; Arregui, G.; Capuj, N. E.; Pitanti, A.; Maire, J.; Griol, A.; Garrido, B.; Martinez, A.; Sotomayor-Torres, C. M.; Navarro-Urrios, D. (Physical review letters, 2019)
The synchronization of coupled oscillators is a phenomenon found throughout nature. Mechanical oscillators are paradigmatic examples, but synchronizing their nanoscaled versions is challenging. We report synchronization of the mechanical dynamics of a pair of optomechanical crystal cavities that, in contrast to previous works performed in similar objects, are intercoupled with a mechanical link and support independent optical modes. In this regime they oscillate in antiphase, which is in agreement with the predictions of our numerical model that considers reactive coupling. We also show how to temporarily disable synchronization of the coupled system by actuating one of the cavities with a heating laser, so that both cavities oscillate independently. Our results can be upscaled to more than two cavities and pave the way towards realizing integrated networks of synchronized mechanical oscillators.